IDENTIFIKASI GAYA PENGAMBILAN KEPUTUSAN MAHASISWA SEBAGAI KONSUMEN BIOSKOP - Yulianto, Aries; Dharmawan, Debby (Jurnal Psikologi, 2018)
AbstractThe drastic increase in the number of movie goers in the cinemas dominated by young adults, especially college students. By making young adultsas a target in the business world, it's important to see how college studentsâ€™ consumerdecision-making styles in watching moviesatcinemas. Previous studies of consumer decision-making styles in young adults have found inconsistent results. This study aims to determine the dominant decision-making style in college students when watching movie at the cinemas. The instrument used was the adaptation of Consumer Style Inventory (CSI) scale from Sproles and Kendall (1986) which measures seven styles. The participants were 225 students (105 men and 210 women) aged 17 to 21 years old from three private universities in West Jakarta. We found â€œPerfectionisticâ€ (36.00%), â€œPrice consciousâ€ (35.11%), and â€œRecreationalâ€ (31.56%) as dominant consumerdecision-making styles. This means that college students tend to prefer the quality of cinema in watching movies as a means of entertainment while still paying attention to ticket prices in their spare time with financial limitations.Â Keywords: college students, movie goers, cinema, consumer decision making styles.Â AbstrakPeningkatan drastis jumlah penonton film di bioskop didominasi oleh orang muda, khususnya mahasiswa.Dengan dijadikannya orang muda sebagai sasaran dalam dunia bisnis, penting untuk melihat bagaimana gaya pengambilan keputusan dalam menonton film di bioskop. Studi-studi sebelumnya mengenai gaya pengambilan keputusan konsumen pada orang muda menemukan hasil yang tidak konsisten. Penelitian ini bertujuan untuk mengetahui gaya pengambilan keputusan yang dominan pada mahasiswa ketika menonton di bioskop. Instrumen yang digunakan adalah adaptasi skala Consumer Style Inventory (CSI) dari Sproles dan Kendall (1986) yang mengukur tujuh gaya. Partisipan penelitian merupakan mahasiswa dari tiga universitas swasta di Jakarta Barat sebanyak 225 mahasiswa (105 laki-laki dan 210 perempuan) berusia antara 17 hingga 21 tahun. Sesuai dugaan peneliti, ditemukan tiga gaya dominanÂ  adalah Perfectionistic (36,00%), Price conscious (35,11%), dan Recreational (31,56%). Artinya mahasiswa cenderung mengutamakan kualitas bioskop dalam menonton film sebagai sarana hiburan dengan tetap memperhatikan harga tiket di waktu luang mereka dengan keterbatasan keuangan.Â Kata kunci: mahasiswa, penonton bioskop, bioskop, gaya pengambilan keputusan konsumen.